MUL-ADHARA: A FUSION OF TRADITIONAL TEXTILES AND FASHION INSPIRED BY THE ROOT CHAKRA - Puri, Archana (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The human body’s chakras are crucial energy centres, with each contributing uniquely to physical, mental, and emotional well-being. Among these, the Muladhar or Root Chakra, located at the base of the spine, is essential. It represents anchoring, stability, and security, and is critical to total equilibrium. When aligned, it promotes resilience, confidence, and emotional strength. The COVID-19 epidemic upset this balance for many people, causing tension, anxiety, and uncertainty. Inspired by the Root Chakra’s grounding energy, the author created a fashion line based on traditional textiles and the spirit of the Muladhar Chakra. These fabrics, with their deep cultural value, represent a connection to legacy and stability. This collection goes beyond creativity, addressing a shared human experience and providing a route to restoring balance and well-being. By combining tradition with design, it emphasizes the continuing strength of our roots, providing both comfort and inspiration.